2016
DOI: 10.1016/j.psychres.2016.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Community-oriented family-based intervention superior to standard treatment in improving depression, hopelessness and functioning among adolescents with any psychosis-risk symptoms

Abstract: The aim of the present study was to compare change in functioning, affective symptoms and level of psychosis-risk symptoms in symptomatic adolescents who were treated either in an early intervention programme based on a need-adapted Family- and Community-orientated integrative Treatment Model (FCTM) or in standard adolescent psychiatric treatment (Treatment As Usual, TAU). 28 pairs were matched by length of follow-up, gender, age, and baseline functioning. At one year after the start of treatment, the matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…The measures taken in OD could ease the difficulties that occur when there are breaks in treatment contact and in decision making, or when the treatment is restarted with staff who are unfamiliar with the patient's specific situation. The results here are in line with other studies, in which better treatment outcomes have been observed in integrative early-intervention systems for acute psychosis (Lehtinen et al, 2000;Cullberg et al, 2006;Granö et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The measures taken in OD could ease the difficulties that occur when there are breaks in treatment contact and in decision making, or when the treatment is restarted with staff who are unfamiliar with the patient's specific situation. The results here are in line with other studies, in which better treatment outcomes have been observed in integrative early-intervention systems for acute psychosis (Lehtinen et al, 2000;Cullberg et al, 2006;Granö et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…These include, for example, early-stage family interventions (Marshall and Rathbone, 2011), with a shortened duration of untreated psychosis (Farooq et al, 2009), and increased therapeutic alliance (Laska and Gurman, 2014). Improved treatment outcomes have also been observed in other early and comprehensive intervention systems (Cullberg et al, 2006; Kane et al, 2015;Granö et al, 2016). Nevertheless, regarding the long-term outcomes of early intervention practices in the treatment of psychoses, research has been limited, and contradictory results obtained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The mean treatment duration was 30.0 weeks (range = 4‐104 weeks.). Interventions included: CRT ( N = 6) (Choi et al, ; Hooker et al, ; Loewy et al, ; Piskulic, Barbato, & Addington, ; Rauchensteiner et al, ; Urben, Pihet, Jaugey, Halfon, & Holzer, ), family‐based treatments ( N = 5) (Grano et al, ; Landa et al, ; McFarlane et al, ; Miklowitz Dj et al, ; O'Brien et al, ), CBT ( N = 6) (Addington et al, ; Kim et al, ; Morrison Ap et al, ; Morrison et al, ; Stain et al, ; van der Gaag et al, ), aripiprazole ( N = 3) (Kobayashi et al, ; Liu et al, ; Woods et al, ), NMDAR modulators ( N = 3) (Kantrowitz et al, ; Woods et al, ), omega‐3 ( N = 3) (Amminger et al, ; Cadenhead et al, ; McGorry et al, ), integrated psychological intervention ( N = 3) (Albert et al, ; Nordentoft et al, ; Wessels et al, ), risperidone plus CBT ( N = 2) (McGorry et al, ; McGorry Pd et al, ), amisulpride ( N = 1) (Ruhrmann et al, ), olanzapine ( N = 1) (McGlashan Th et al, ), low‐dose lithium ( N = 1) (Berger et al, ), ziprasidone ( N = 1) (Woods et al, ), perospirone ( N = 1) (Tsujino et al, ), second generation anti‐psychotics ( N = 1) (Cornblatt et al, ), anti‐psychotics not specified ( N = 3) (Morita et al, ; Shim et al, ; Walker et al, ) and heart rate variability biofeedback training ( N = 1) (McAusland & Addington, ). The control conditions varied as well; placebo ( N = 8), computer games ( N = 4), needs‐based interventions ( N = 12), supportive therapy ( N = 3) and enhanced care ( N = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Interventions included: CRT (N = 6) (Choi et al, 2016;Hooker et al, 2014;Loewy et al, 2016;Piskulic, Barbato, & Addington, 2012;Rauchensteiner et al, 2011;Urben, Pihet, Jaugey, Halfon, & Holzer, 2012), family-based treatments (N = 5) (Grano et al, 2016;Landa et al, 2016;McFarlane et al, 2015;Miklowitz Dj et al, 2014;O'Brien et al, 2007), CBT (N = 6) (Addington et al, 2011;Kim et al, 2011;Morrison Ap et al, 2004;Morrison et al, 2012;Stain et al, 2016;van der Gaag et al, 2012), aripiprazole (N = 3) (Kobayashi et al, 2009;Liu et al, 2013;Woods et al, 2007) Thirteen studies did not use a control group.…”
Section: Features Of Treatment Interventions and Controlsmentioning
confidence: 99%
“…12 This is a notable contrast to the field of psychosis, in which a large proportion of research resources has been targeted at understanding, recognizing, and managing early-stage disease. [24][25][26][27] The objective of this article was to provide a comprehensive review of the literature on neurobiology of the early stages of BD, with a special focus on the late prodromal stage and the period surrounding the first episode of mania. We also aimed to discuss the implications of emerging research findings in this field for investigation and clinical care.…”
Section: Introductionmentioning
confidence: 99%